Faktor – faktor yang Memengaruhi Penerimaan Opini Audit Going Concern: Studi Empiris Pada Perusahaan Property dan Real Estate di BEI - Khoirun Nisa' Nur Hasanah; Rina Trisnawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Going concern audit opinion is an accounting statement to ensure the survival of a company's business issued by the auditor. This study aims to determine the effect of company growth, opinion shopping, funding decisions, institutional ownership, prior opinion, and company size on going concern audit opinion acceptance. The object of research is 92 property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the period 2020-2023. Going concern audit opinion is calculated using dummy variables. The sample collection method used purposive sampling and obtained a sample of 56 companies, so that the total sample obtained was 224 samples. Data analysis was carried out with SPSS statistical tools using multiple linear regression analysis methods. The results showed that the variables of company growth and company size had no effect on going concern audit opinion acceptance, while the variables of opinion shopping, funding decisions, institutional ownership, and prior opinion had an effect on going concern audit opinion acceptance.